Zarządzanie strategiczne w regionie - koncepcja foresight regionalnego dla województwa podkarpackiego - Woźniak, Leszek; Ziółkowski, Bożydar (Strategie management in a region - regional foresight conception for subcarpathian voivodship, 2006)
In the article there was presented the theory and assumptions of foresight activities with putting of special attention on regional solutions. Earlier prepared regional innovation strategy may be the first step in creating of regional foresight for Subcarpathian Voivodship.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 315-321